MERAWAT MISTISISME DALAM TRADISI NGALAP BERKAH SEBAGAI PENGABDIAN DALAM MENJAGA HUBUNGAN SOSIAL BERMASYARAKAT DI ERA MODERN - aderitonga; Indonesia (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Mysticism as an expression of spirituality has long existed in Indonesian society, and one manifestation of this is evident in the tradition of ngalap berkah (the practice of offering blessings). This tradition is seen not merely as a mystical ritual practice but also as a means of maintaining social harmony and strengthening community solidarity. This article aims to examine how the mystical practice of ngalap berkah functions as an effort to maintain social relations in the modern era, which tends towards individualism. The research was conducted using a qualitative approach through initial observation and literature review, emphasizing descriptive-analytical methods to understand the cultural, religious, and social contexts of the practice. The results indicate that the practice of ngalap berkah can serve as a bridge between Sufism and local traditions, thus not only fostering individual spirituality but also creating a space for friendship, togetherness, and social cohesion. In a modern society characterized by rationalization and the rapid flow of globalization, the existence of this tradition remains relevant because it presents values of local wisdom that can balance spiritual and social needs. Furthermore, the ngalap berkah tradition also functions as a cultural mechanism to reduce conflict, foster a sense of togetherness, and strengthen the community's collective identity. Thus, nurturing mysticism through the tradition of seeking blessings not only means preserving religious cultural heritage, but also provides a strategic solution in maintaining social harmony amidst the challenges of modernity.